Light Field‐Enhanced Single‐Site Cu Electrocatalyst for Nitrogen Fixation. Issue 10 (15th January 2023) - Zhao, Zhi‐Qiang; Li, Kai; Liu, Jia; Mao, Jun‐Jie; Lin, Yu‐Qing
Abstract: Direct electrocatalytic reduction of N2 to NH3 under mild conditions is attracting considerable interests but still remains enormous challenges in terms of respect of intrinsic catalytic activity and limited electrocatalytic efficiency. Herein, a photo‐enhanced strategy is developed to improve the NRR activity on Cu single atoms catalysts. The atomically dispersed Cu single atoms supported TiO2 nanosheets (Cu SAs/TiO2 ) achieve a Faradaic Efficiency (12.88%) and NH3 yield rate (6.26 µg h −1 mgcat −1 ) at −0.05 V versus RHE under the light irradiation field, in which NH3 yield rate is fivefold higher than that under pure electrocatalytic nitrogen reduction reaction (NRR) process and is remarkably superior in comparison to most of the similar type electrocatalysts. The existence of external light field improves electron transfer ability between CuO and TiO, and thus optimizes the accumulation of surface charges on Cu sites, endowing more electrons involved in nitrogen fixation. This work reveals an atomic‐scale mechanistic understanding of field effect‐enhanced electrochemical performance of catalysts and it provides predictive guidelines for the rational design of photo‐enhanced electrochemical N2 reduction catalysts. Abstract : Here, a photo‐enhanced strategy is exhibited to improve the NRR activity for Cu SAs/TiO2 . Coupled with light, the Cu single‐atoms can enrich photo‐generated electrons and enhance the N2 adsorption capacity. The special CuOTi structure is conducive to the transfer toward electrons and photo‐generated electrons. This research provides a blueprint for the design of photo‐enhanced electrocatalysts at the atomic scale.